KINERJA OPERASI KERETA API BARAYA GEULIS RUTE BANDUNG-CICALENGKA - Dewi Rosyani; Budi Hartanto Susilo (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2011)
Baraya Geulis Train Service is local business class passenger train with a route serving Bandung-Cicalengka. In this study, the performance of train operations are assessed, which include operating speed, timeliness, load factor, headway, and comfort on the train. The results show that, in general, the operating performance of the Baraya Geulis Train is quite well and in compliance with existing standards. Only the operating speed of this train needs to be improved so that it can meet the minimum operating speeds, which is 60 km/hour.Keywords: train operational performance, local trains, operation speed.